SURGICAL EQUIPMENTS FOR PEARL CULTURE - Alagarswami, K; Sivarajan, G S (Indian Journal of Fisheries, 2011)
Hie present communication describes the surgical instruments developed indigenously for the first time at the Surgical Instruments Plant. The material used in all cases is stainless steel of straight chromium type conforming to I.S.I, specification 30 CR 13 and 40 CR 13. The items are fabricated to fine dimensional accuracy and surface finish. Fig. 1 illustrates the instruments developed indigenously.